A critical analysis and comparison of two series of second language English Readers in use in the schools of the Cape Province - Van Heerden, J. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- Universiteit van Stellenbosch, 1944.